World Health Organisation staging, adherence to HAART and abnormal cervical smears amongst HIV-infected women attending a government hospital in Johannesburg, South Africa. Issue 4 (25th November 2016) - Ciamalenga Katumba, Appolinaire; Reji, Elizabeth; Gitau, Tabither; Firnhaber, Cindy
Abstract : Introduction: South Africa (SA) has more people living with Human Immunodeficiency Virus (HIV) than any other country in the world. Women infected with HIV have a higher risk of developing cervical dysplasia and cancer than women who are not infected. Objective: To ascertain the correlation between the World Health Organisation (WHO) HIV staging and adherence to highly active antiretroviral therapy (HAART) with abnormal Pap smear results of HIV-infected women attending a government hospital in Johannesburg, SA. Methods: A cross-sectional descriptive study was performed by reviewing Pap smears of 390 HIV-positive women. Adherence was measured by the patient's report and viral load. Data was collected through the use of self-administered questionnaires. Results: The prevalence of abnormal Pap smears was 57% and low grade squamous intraepithelial lesions (LGSIL) were the most common abnormality seen (142/390, 36%). WHO stage 3 participants were three times more likely to have abnormal Pap smears than those with WHO stage 1 (OR 3.3, 95% CI 1.23-9.04, p = 0.018). Abnormal Pap smears were seen more frequently in participants with a CD4 cell count ≤ 350 cells/μl compared to participants with CD4 cell count ≥ 500 cells/μl ( p = 0.001, 95% CI 0.09-0.37). Participants who did not use HAART had more abnormal results compared to those who used HAART ( p < 0.028, 95% CI 0.28-0.93). Self-reported adherence to HAART did not show any association with abnormal Pap smears. Conclusion: Increased immune-suppression measured by WHO staging or CD4 count increases the risk of cervical cancer precursors. The high risk group in this study was found to be participants with CD4 < 350 cells/μl.